2022
DOI: 10.3390/healthcare10061067
|View full text |Cite
|
Sign up to set email alerts
|

Hypothetical Model of How a Clinical Remount Procedure Benefits Patients with Existing Dentures: A Narrative Literature Review

Abstract: The clinical remount procedure, which involves remounting the dentures on an articulator with interocclusal records, can effectively reduce occlusal discrepancies. This procedure can be applied not only to new dentures but also to those already in service; however, research in this field is still scarce. This narrative review aims to establish a hypothetical mechanism and possible indications and contraindications for this technique as a basis for further research. Current studies have revealed a high prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…This study aimed to reveal the merits of performing clinical remount procedures on existing dentures by assessing patients’ OHRQoL. According to the previous review, rebalancing of the occlusion was indicated only if patients reported occlusion-related complaints with their existing dentures [ 7 ]. Therefore, it would be extremely difficult and unethical to intentionally create such niche treatment needs to conduct well-controlled, prospective research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study aimed to reveal the merits of performing clinical remount procedures on existing dentures by assessing patients’ OHRQoL. According to the previous review, rebalancing of the occlusion was indicated only if patients reported occlusion-related complaints with their existing dentures [ 7 ]. Therefore, it would be extremely difficult and unethical to intentionally create such niche treatment needs to conduct well-controlled, prospective research.…”
Section: Discussionmentioning
confidence: 99%
“…Previous review examined the extraoral method, also known as the clinical remount procedure, an accurate and efficient way to correct cumulative errors in the jaw relationship [ 7 ]. Schierano et al reported that a patient’s thickness discrimination ability was enhanced after a clinical remount was performed on existing dentures [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are many options available to ensure a physiological dentition, such as traditional dentures, implant-supported fixed prosthesis, and implant-retained removable overdenture [12][13][14][15][16][17]. Traditional dentures are no longer considered an adequate therapeutic choice [14,18].…”
Section: Introductionmentioning
confidence: 99%
“…Because of these characteristics, the literature investigating overdenture has increased in the past years. Several studies have evaluated the correlation between the retention strength of the attachments and the stability of the prosthesis, the quality of masticatory function, and the patient satisfaction [13,[29][30][31]. Different research focused on the characteristics of attachments, such as material, design, and dimensions.…”
Section: Introductionmentioning
confidence: 99%